Noncommunicable Diseases A Compendium - Banatvala, Nick; Bovet, Pascal (Taylor & Francis, 2023)
Noncommunicable Diseases: A Compendium introduces readers to noncommunicable diseases (NCDs) - what they are, their burden, their determinants and how they can be prevented and controlled. Focusing on cardiovascular disease, diabetes, cancer and chronic respiratory disease and their five shared main risk factors (tobacco use, harmful use of alcohol, unhealthy diet, physical inactivity and air pollution) as defined by the United Nations, this book provides a synopsis of one of the world's biggest challenges of the 21st century. NCDs prematurely claim the lives of millions of people across the world every year, with untold suffering to hundreds of millions more, trapping many people in poverty and curtailing economic growth and sustainable development. While resources between and within countries largely differ, the key principles of surveillance, prevention and management apply to all countries, as does the need to focus resources on the most cost-effective and affordable interventions and the need for strong political will, sufficient resources, and sustained and broad partnerships. This compendium consists of 59 short and accessible chapters in six sections: (i) describing and measuring the burden and impact of NCDs; (ii) the burden, epidemiology and priority interventions for individual NCDs; (iii) social determinants and risk factors for NCDs and priority interventions; (iv) global policy; (v) cross-cutting issues; and (vi) stakeholder action. Drawing on the expertise of a large and diverse team of internationally renowned policy and academic experts, the book describes the key epidemiologic features of NCDs and evidence-based interventions in a concise manner that will be useful for policymakers across all parts of society, as well as for public health and clinical practitioners.